trigon 85 : Synonyme für Skulptur. - Künstlerhaus Neue Galerie, Graz (Graz : Neue Galerie am Landesmuseum Joanneum, 1985)
Ceccobelli, Bruno ; Toraldo, Gian Luca Giorgetti ; Gnozzi, Roberto ; Nunzio ; Ontani, Luigi ; Zutic, Stevan ; Mohorovicic, Andre ; Pocivavsek, Matjaz ; etc.
trigon 85 : Synonyme für Skulptur, Künstlerhaus Neue Galerie, Graz, 21.9. - 13.10.1985
boek